2019
DOI: 10.1002/jcp.28021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of Cks1 in cancer: Evidence from a meta‐analysis

Abstract: Background Cyclin‐dependent kinase subunit 1 (Cks1), as a highly conserved regulatory protein, has pleiotropic roles in cell cycle progression. As research progresses, increasingly more statistics show that Cks1 may be involved in the occurrence, development, and prognosis of a variety of tumors but the conclusions remain controversial. In addition, there has been no meta‐analysis demonstrating the correlation between Cks1 and cancer. Therefore, this meta‐analysis was performed to determine the prognostic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…To our surprise there were no significant CNAs differences in FGFR3 and CSF1R between pNETs and sbNETs using FISH and logistic regression analyses even though we observed significant CNA differences in our CMA data discovery cohort. Secondly, CKS1B copy number gain was not associated with PFS in this study but has been correlated with poor PFS in pan-cancer analyses [46][47][48][49][50][51][52]. It is important to note that those studies did not include assessing the correlation between GEP NET prognosis and CKS1B copy number status.…”
Section: Discussionmentioning
confidence: 75%
“…To our surprise there were no significant CNAs differences in FGFR3 and CSF1R between pNETs and sbNETs using FISH and logistic regression analyses even though we observed significant CNA differences in our CMA data discovery cohort. Secondly, CKS1B copy number gain was not associated with PFS in this study but has been correlated with poor PFS in pan-cancer analyses [46][47][48][49][50][51][52]. It is important to note that those studies did not include assessing the correlation between GEP NET prognosis and CKS1B copy number status.…”
Section: Discussionmentioning
confidence: 75%
“…The global cancer burden in 2040 is expected to increase to 28.4 million cases due to changing demographics and increasing risk factors along with globalization (Sung et al, 2020). The high mortality rate in cancer patients, particularly solid cancer, but the low number of survivors, prompts improvements in treatment and screening efforts to identify factors such as stage, grade, tumor size, and metastases early (Oeffinger et al, 2013;Giraldo et al, 2019;Zhang et al, 2019). However, these clinicopathological factors are not fully a tool to determine the outcome of the condition of cancer patients, including solid cancer (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the role of high USP39 expression on the prognosis and clinicopathological characteristics of patients with solid cancer and found varying results between studies (Zhang et al, 2019;Kisai and Koji, 2021). Different assessment methods certainly show the potential for different biases between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al found that CKS1B silencing inhibites cell proliferation and invasion and activates apoptosis in glioma (7). In addition, a meta-analysis including 2,224 cancer participants showed that high CKS1B expression is associated with advanced T stage and lymph node metastasis (8). These evidences suggest that CKS1B may be a key gene to promote the malignant progression in a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%